Pengaruh Bionematisida Berbahan Aktif Jamur Paecilomyces lilacinus Strain 251 terhadap Serangan Pratylenchus coffeae pada Kopi Robusta - Soekadar Wiryadiputra (Jurnal Perlindungan Tanaman Indonesia, 2002)
Experiment on the effect of P. lilacinus on the infestation of P. coffeae on robusta coffee was conducted in Sumber Asin Experimental Garden, Malang. The treatments were dosages of bionematicide i.e. : 0 (control), 0.25, 0.50, 1.00, 2.00, and 4.00 g; carbofuran (3 % active ingredient) 50 g/plant and organic soil treatment (OST) at 100 g/plant. Each treatment was replicated four times, and each replication consists of five coffee trees. The results in second year observation revealed that the population of P. coffeae in the roots on PL 251 treatments was not significantly different compared to the control, whereas in soil samples the population of both P. coffeae and Rotylenchulus reniformis inclined to be lower than the control, although they were not statistically significant. The lowest infestation was observed on PL 251 treatment at a dosage level of 4.00 g/tree. On nematode infestation, no significant difference on treatments of carbofuran and OST compared to the control. The yield of green coffee (market coffee) was the highest on the treatment of PL 251 at a dosage of 4.00 g/tree and significantly higher than the control and carbofuran treatments, with increasing levels of 225.3 and 198.9%, respectively.